Lawsuit Against the Regent of Mandailing Natal Over the Location Permit for Plasma Land from the Perspective of Fiqh Siyasah (Analysis Study of Ptun Decision Number 84/G/2018/Ptun.Mdn) - Hamid, Ikmal; Firmansyah, Heri (IHSA Institute, 2025)
Land or territory is the main element of a country. In the perspective of fiqh siyasah, which regulates politics and government in Islam, land dispute cases on Batahan Plasma land as occurred in the case at the Medan PTUN can be seen as part of the leader's responsibility in maintaining justice and preventing conflict in society. The purpose of the study was to find out how the Lawsuit Against the Regent of Mandailing Natal Over the Location Permit for Plasma Land from the Perspective of Fiqh Siyasah (Analysis Study of Ptun Decision Number 84/G/2018/Ptun.Mdn). Research method, Normative Law research. The results of the study, PTUN Decision Number 84/G/2018/PTUN.MDN which granted the lawsuit against the Regent of Mandailing Natal regarding the location permit for Batahan Plasma Land shows the importance of the principles of legality, justice, and public interest in government administrative actions. The Medan PTUN assessed that the permit issued by the Regent was unlawful, not through a legitimate procedure. In the perspective of fiqh siyasah, this decision reflects an effort to uphold justice, transparency, and accountability, which is in line with the principles of social justice and public responsibility. This emphasizes the role of the court in ensuring that public policies are carried out for the public interest, not for the interests of individuals or certain groups. Accurate data certainly leads to transparency and minimizes the potential for fraud in the 2024 elections